The Poetics and Politics of Interruption in the 2020-21 Belarus Uprising - Sosnovskaya, Olia (Atlantis)

(untitled) (Mount Saint Vincent University, 2023)
The paper addresses the notions of interruption and exhaustion in relation to the 2020–21 anti-governmental uprising in Belarus. It examines various forms of protesting, such as marches, neighbourhood gatherings and strikes from a feminist perspective. It focuses on the dynamics of visibility and opacity, social reproduction and politicization of mundane gestures, and on questioning the notion of revolutionary event and its temporalities.